Efektifitas Perawatan Metode Kangguru (PMK) dan Terapi Murottal terhadap Peningkatan Berat Badan dan Suhu pada Bayi BBLR - Putriana, Yeyen; Aliyanto, Warjidin (Politeknik Kesehatan Tanjungkarang, 2018)
Infants with low birth weight (LBW) are at high risk of health problems. LBW infants require special care to minimize the risk of infant mortality. LBW treatments apart from the treatment in the incubator and kangaroo mother care (KMC). This study was to determine the increase in body weight and body temperature through murottal therapy as one of the stimulations of nursing LBW infants. The research design was quasi-experimental with pretest control group design. The study was conducted at Dr. H Abdul Moeloek Hospital (RSUAM) Bandar Lampung. The population of the study was all babies of LBW treated in the RSUAM Perinatology Room. Sampling technique was using probability sampling. The sample size was determined using different hypothesis test formula. The results showed there were differences in weight and body temperature increase on days II, III and IV in the intervention group. This study recommends the use of morottal therapy in the treatment of LBW with KMC. Because therapy morottal system works similar to therapy music that causes a sense of comfort and improves sleep patterns baby.